Security Informatics - Chen, Hsinchun
Intelligence and Security Informatics (ISI) is defined as the development of advanced information technologies, systems, algorithms, and databases for international, national and homeland security related applications, through an integrated technological, organizational, and policy-based approach (Chen 2006). Security Informatics will publish peer-reviewed articles in areas relevant to ISI research, from the perspectives of Information Technology/ Informatics and related policy considerations. Paper selection will focus on articles that present innovative research ideas and results, report significant application case studies, provide tutorial surveys, and raise awareness of pressing research and application challenges.